Kawasaki disease in children: diagnosis, treatment, and therapeutic guidelines in light of a clinical case - Mateusz Heba; Aleksandra Kocjan; Elżbieta Rychlicka; Jakub Kozłowski; Alicja Kamińska; Bartłomiej Żaczek; Marta Czubaj-Kowal (Annales Academiae Medicae Silesiensis, 2025)
Kawasaki disease (KD) is an acute inflammation of small- and medium-sized arteries of unknown etiology. It most commonly affects children under the age of 5, with a peak incidence at 2 years of age. Because of its nonspecific symptoms, the diagnostic process is prolonged and challenging. The primary symptoms include a high fever persisting for more than 5 days, lymphadenopathy, and skin changes. Other symptoms may include mucosal redness and cracking, “strawberry tongue”, conjunctivitis, swelling of the hands and feet with sheet-like peeling of the skin, and desquamation in the perineal area. This article presents the case of a 2-year-old boy admitted to the pediatric department of a hospital due to a high fever lasting several days, elevated inflammatory markers, and diarrhea. During hospitalization, new symptoms were observed, allowing the diagnosis of incomplete Kawasaki syndrome. The patient was treated according to European standards with a favorable therapeutic outcome and was monitored in a cardiology clinic. The boy was discharged in good condition without complications. This case highlights KD as both a diagnostic and therapeutic challenge, especially in its incomplete and atypical forms.